2013
DOI: 10.1186/1471-2393-13-235
|View full text |Cite
|
Sign up to set email alerts
|

Reliability tests and validation tests of the client satisfaction questionnaire (CSQ-8) as an index of satisfaction with childbirth-related care among Filipino women

Abstract: BackgroundSatisfaction is an important indicator of the quality of care during childbirth. Previous research found that a good environment at a health facility can increase the number of deliveries at that facility. In contrast, an unsatisfying childbirth experience could cause postpartum mental disorder. Therefore it is important to measure mothers’ satisfaction with their childbirth experiences. We tested whether the eight-item Client Satisfaction Questionnaire (CSQ-8) provided useful information about satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…To assess feasibility and acceptability, we used the modified version of the Client Satisfaction Questionnaire (CSQ)-8 to fit the context of the use of the psychoeducation intervention (PERANTARA) in Indonesia. The original CSQ-8 has eight questions assessing the global client's satisfaction in a clinical setting (Larsen et al, 1979;Matsubara et al, 2013). The patients respond to those items using a 4-point Likert scale, and the total scores range from 8 to 32.…”
Section: Instrumentsmentioning
confidence: 99%
“…To assess feasibility and acceptability, we used the modified version of the Client Satisfaction Questionnaire (CSQ)-8 to fit the context of the use of the psychoeducation intervention (PERANTARA) in Indonesia. The original CSQ-8 has eight questions assessing the global client's satisfaction in a clinical setting (Larsen et al, 1979;Matsubara et al, 2013). The patients respond to those items using a 4-point Likert scale, and the total scores range from 8 to 32.…”
Section: Instrumentsmentioning
confidence: 99%
“…Overall patient satisfaction (CSQ-8) was high in literature comparison: median scores between 26 and 27 have been report from childbirth related care, family and mental health care. 21,22 As a limitation, CSQ-8 scores were not measured for children receiving conventional care only. The relatively low response rate to the questionnaire was mainly a result of failing to consistently distribute the questionnaire at the end of hospitalization rather than a lack of parental unwillingness to respond.…”
Section: Discussionmentioning
confidence: 99%
“…Global client satisfaction with the internet-and mobile-based intervention is measured by eight items. Previous research indicated good psychometric properties (α = 0.84-0.97) (70).…”
Section: Training and Acceptabilitymentioning
confidence: 97%